2021
DOI: 10.4149/av_2021_201
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory syndrome coronavirus 2 invasion in the central nervous system: a host-virus deadlock

Abstract: the SArS-CoV-2 devastation on the Center Nervous System (CNS) is ascertained by the present clinical findings and the noticeable signs and symptoms. the CNS involvement of the virus is not trivial; something considered the most destructive potential of the virus as the brain evolves into a highly protective structure. different possible routes with favorable mechanisms are used by the virus to have a successful entry. then, the SArS-CoV-2 invasion illustrates a mechanism of both the innate and adaptive immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Nevertheless, recent pooled evidence has consistently reported that chronic diseases like chronic obstructive pulmonary disease (COPD), cardiovascular disease (CVD), cancer, cerebrovascular accident (CVA), diabetes, hypertension, and chronic kidney disease have an association with the severity among COVID-19 patients (Baral et al 2021). So, polyunsaturated fatty acids may have an essential role in lessening the risk of these comorbidities and improving the health of COVID-19 positive cases (Asher et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent pooled evidence has consistently reported that chronic diseases like chronic obstructive pulmonary disease (COPD), cardiovascular disease (CVD), cancer, cerebrovascular accident (CVA), diabetes, hypertension, and chronic kidney disease have an association with the severity among COVID-19 patients (Baral et al 2021). So, polyunsaturated fatty acids may have an essential role in lessening the risk of these comorbidities and improving the health of COVID-19 positive cases (Asher et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies suggested that corticostreids should be prescribed with caution in this patients, recent investigations revealed that these patients should receive corticosteroids due to possible benefits (82)(83)(84). These patients could be administered with intravenous human immunoglobulins (IVIG), plasma exchange (PLEX), and immunotherapy if possible (85). Based on Vaschetto et al study, IVIG and thereafter prescription of methylprednisolone improved cerebral nervous system vasculitis in a COVID-19 patient (13).…”
Section: Treatment and Management Of Patients With Cns Autoimmune Dis...mentioning
confidence: 99%
“…8 In the central nervous system (CNS), the removal of the virus from the tissues by the innate and adaptative immune responses could result in neurological damage. 9 The innate immune system has been shown to have a major role in the acute phase of infection. Namely, immune effector cells have been shown to release pro-inflammatory cytokines and chemokines, a cocktail that potentiates further systemic inflammation and may ultimately culminate into a cytokine storm.…”
Section: Myelitis or Polyradiculoneuropathy In Thementioning
confidence: 99%